2016
DOI: 10.1007/s12010-015-1954-y
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Expression and Characterization of a New scFv Directed to Human CD123

Abstract: Leukemic cancer stem cells (LSCs), as a unique cell population in acute myeloid leukemia (AML) marked by CD123 overexpression, are thought to play a key role in relapsed AML after chemotherapy. Thus, CD123 is considered as a particularly important target candidate for antibody-derived diagnosis and therapy. In the present work, we constructed an immunized murine antibody phage display library and isolated the functional anti-CD123 Single-chain fragment variable (scFv) clones. We also introduced fusing variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Consistent with our study, Qiyu Sun et al showed that 7G3, raised against CD123, specifically binds to the IL-3R a-chain; more importantly, the mAb 7G3 was demonstrated to inhibit IL-3-mediated proliferation of leukemic cell lines [3]. Consistent with our findings, Moradi-Kalbolandi et al showed that purified scFv could specifically recognize CD123 by ELISA and flow cytometry, with no cross-reactivity with related cell markers [1]. The absence of cross-reactivity and high binding capacity of our mAb make it a potential tool for detection or even clinical applications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our study, Qiyu Sun et al showed that 7G3, raised against CD123, specifically binds to the IL-3R a-chain; more importantly, the mAb 7G3 was demonstrated to inhibit IL-3-mediated proliferation of leukemic cell lines [3]. Consistent with our findings, Moradi-Kalbolandi et al showed that purified scFv could specifically recognize CD123 by ELISA and flow cytometry, with no cross-reactivity with related cell markers [1]. The absence of cross-reactivity and high binding capacity of our mAb make it a potential tool for detection or even clinical applications.…”
Section: Discussionsupporting
confidence: 91%
“…Acute myeloid leukemia (AML), a cancer of the myeloid line of blood cells, is an aggressive malignancy of the bone marrow . AML is characterized by a cell maturation arrest, uncontrolled proliferation, and subsequent accumulation of undifferentiated myeloid blasts in bone marrow, blood, and other tissues, interfering with the production of normal blood cells . Although most patients with AML can be effectively treated with a standard chemotherapy regimen, relapsed AML remains a major problem .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we creatively developed an adenovirusmediated anti-AEG-1 ScFv expression system driven by stathmin promoter. Actually, due to its antigen-targeting and high-affinity, ScFv is supposed to be widely deployed involving various aspects, especially tumor targeting therapy [13,14,18]. A recent study has displayed a good result of ScFv in AML that ScFv against EphA2 have specific cytotoxicity effect on AML with EphA2 overexpression [13].…”
Section: Discussionmentioning
confidence: 99%